Value Creation in PPP Projects Undertaken in the Turkish Healthcare Industry - Erk, Eralp Yueksel; Budayan, Cenk; Koc, Kerim; Tokdemir, Onur Behzat (ASCE-AMER SOC CIVIL ENGINEERS, 2023)
Due to the capacity deficits of the healthcare sector, governments faced many difficulties when responding to the burden caused by the COVID-19 pandemic. Private sector involvement in healthcare facilities delivery enabled through public-private partnerships (PPPs) can play a crucial role in overcoming these capacity deficits. Although PPP projects can help to overcome infrastructure deficiencies, some are criticized due to the low value created for stakeholders. These include not only society in general, which uses the healthcare facilities, but also the project participants. Value generation for the latter is also an essential objective of PPP healthcare projects in a generic view, which is often neglected. This study aims to understand value creation in healthcare PPPs by developing a framework based on concepts related to the project value and eventually proposing a business model to maximize the generated value at the organizational level for all stakeholders. In order to achieve the study objective, insights are obtained from a literature survey, semistructured interviews, and focus group discussions. A value-creation model consisting of components and subcomponents of value generation and the relationship between these is proposed. The model demonstrates that the process component plays a central role in value creation, requiring sufficient assets of the parties engaged in and the appropriate governance of PPP projects. The value-creation model proposed here further highlights the driving role of a well-balanced legal framework and organizational learning. All the identified subcomponents are found to be interrelated, highlighting the importance of the proposed business model design in value creation. Overall, given the lack of healthcare facility capacity in many countries and the need to create value in healthcare PPP attempts, the proposed value-creation model is expected to help project participants develop a more value-centric way of managing, controlling, and operating these projects.
Keywords: Value creation; Business model design; Public-private partnership (PPP); Healthcare facilities; PUBLIC-PRIVATE PARTNERSHIPS; BUSINESS MODELS; VALUE CAPTURE; URBAN RAIL; MANAGEMENT; FRAMEWORK; RISK; IMPLEMENTATION; METHODOLOGY; PERFORMANCE; Construction & Building Technology; Engineering